Maxim of Politeness Found in the Characters’ Conversation in Turning Red Movie - Komang Dian Puspita Candra; Dewiyani, Miasari (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
The aims of this research is to analyze the types of politeness maxims produced by the characters in Tuning Red Movie. The data in this research focuses on the utterances obtained from the conversations between the characters. This research used qualitative descriptive method to analyze the types of politeness maxim. The stages of data collection started from downloading the movie from the internet and then watching it repeatedly to understand the contents of the film. Next, take notes on every utterance spoken by the characters that can be used as data to clarify the types of politeness maxims. The last, categorize these utterances into six types of politeness based on Leech (1983) theory. The results of this research indicate that there are six types of politeness maxims used in this movie. First type is tact maxim, second type is generosity maxim, third is Approbation maxim, fourth is modesty maxim, fifth is agreement maxim and last type is symphaty maxim. It can be concluded that the movie contains all types of politeness maxim with their respective purpose.